Earnings management : background, criticisms and answers / Hamid Pourjalali, Takiah Mohd. Iskandar and Aini Aman - Pourjalali, Hamid; Mohd. Iskandar, Takiah; Aman, Aini (Faculty of Accountancy & Accounting Research Institute (ARI), 2002)
In a series of speeches to the financial community during 1998, U.S. Securities and Exchange Commission's former Chairman Arthur Levitt, declared war on "improper earnings management, big bath restructuring charges, and cookie-jar reserves". Current news about firms such as Enron has also brought attention to both how and why managers manage earnings. Accounting numbers form a fundamental part of an organization's efficient contracting technology Many of the terms, conditions, and covenants found in contracts use accounting variables, contractual arrangements and the associated contracting costs as the major determinant of accounting method choice (hence earnings management). Thus, using the propositions of contracting theory, it is possible to predict and explain accounting choices. In this paper we will provide evidence from the literature that companies have the ability to manage (manipulate) earnings using Generally Accepted Accounting Principles (GAAP). Different reasons for this manipulation are mentioned, viz., the existence of contracts among the firms, external/internal parties and the market pressure for firms to perform at an expected level. The paper also provides a review of literature on earnings management in an international setting (such as in Japan). The model suggested in this paper can be used to test contracting and market pressure theories in Malaysia.